Determination of the Critical Period of Cyper-diforceÂ® Treatment against Arthropod fauna and Productivity of Watermelon - Okrikata, Emmanuel; Ogunwolu, Emmanuel Oludele (Iraqi Journal of Science, 2019)
Watermelon has been reported to be vulnerable to insect pest pressure throughout its growth stages with a resultant indiscriminate calendar-based insecticide application (of up to 25 sprays/season in the study area), with its attendant consequences. In order to recommend the crop growth period(s) to effect chemical control measures that will give better return on investment, field trials were set-up in the early- and late-cropping seasons of 2016 and 2017. Forty, 5m long x 8m wide plots were demarcated in randomized complete block design in 4 replications. Treatments were applications of 0.5% Cyper-diforceÂ® (Cypermethrin 30g/L + Dimethoate 250g/L) at seedling, mid-vegetative, mid-flowering, mid-fruiting stages and their combinations. Unsprayed plots served as control. Pest and beneficial arthropod density, leaf injury, crop growth and yield data were collected and subjected to variance analysis and significantly different means were separated by SNK at 5% level of probability. Cost:benefit ratios of the various treatments was also computed. Findings indicate that, leaf-eating beetles had the highest impact on stand survival and yield. Insect pest density and damage generally decreased with increase in frequency of insecticide application and treatment differences were significant (p< 0.05) except in the case of A. gossypii in the late-sown crop of 2017. Plot sprayed at seedling + vegetative + fruiting stages gave the highest fruit yield and return on investment. It is therefore suggested that, for economic production of watermelon, the crop should not be sprayed during the flowering period.